Pelatihan Kader Kesehatan untuk Prevensi Penyebaran Penyakit HIV/AIDS pada Ibu Rumah Tangga di Batujajar Timur Bandung Barat - Patricia Gita Naully; Perdina Nursidika; Indria Astuti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
An increasing number of people living with HIV/AIDS among housewives is increasing every time. Providing education to women in terms of reproductive health rights and fighting stigma against people with HIV/AIDS (PLWHA) is the key to prevention. Community service aims to provide training to housewives in the context of prevention of the spread of HIV/AIDS in housewives. The method of community service is done by presenting material in the form of lectures and learning media. Participants are given a pretest and post-test to assess the effectiveness of the training. The results of community service show that all participants can take part in the training and improve in terms of knowledge. All participants will also conduct similar training on other housewives. Conclusion Housewife training activities to prevent the spread of HIV/AIDS can increase understanding of the disease. Further service is expected to be continued with cadres participating in the training, who can provide training to other housewives.